Transformasi Manajemen Pendidikan Berbasis Data: Telaah Implementasi EMIS dalam Pengelolaan Informasi Madrasah: Data-Based Education Management Transformation: Review of EMIS Implementation in Madrasah Information Management - Yulianto, Irfan; Nurfuadi, Nurfuadi; Yahya, M. Slamet (Institut Agama Islam Daruttaqwa Gresik, 2025)
Today, the development of communication and information processes is technology-based, including in Islamic educational institutions. In response to advancements in information technology, the Ministry of Religious Affairs, through the Decree of the Director General of Islamic Education Number 5974 of 2019, established regulations regarding the use of the Education Management Information System (EMIS) application as an educational management information system. Aligned with the importance of information flow within an institution, Islamic educational institutions are increasingly required to utilize and manage information systems effectively and efficiently. The purpose of this study is to describe and analyze the implementation of the Education Management Information System (EMIS) as a management information system at MI Muhammadiyah Kalipetung, Banyumas Regency. This study employs a descriptive, qualitative research method, drawing on sociological and psychological approaches. Data were obtained through interviews with the principal, the school operator, teachers, and students at MI Muhammadiyah Kalipetung, Banyumas Regency, as well as through observation and documentation. The data sources consist of primary and secondary data. The research process included data collection, data presentation, data reduction, and conclusion drawing. The results indicate that the implementation of the Education Management Information System (EMIS) as a model of educational management information system—analyzed from the resource aspects of staff, information, authority, and facilities—has been effectively implemented at MI Muhammadiyah Kalipetung, Banyumas Regency. The implementation of EMIS is considered successful and beneficial for all related parties, contributing to improvements in educational quality and standards at MI Muhammadiyah Kalipetung.